PHYSICAL EDUCATION OF SCHOOL-AGE CHILDREN - Abdullayev Dilshod Xamidullo o’g’li (American Journals Publishing, 2022)
This article talks about physical education lessons for school-aged children, their organization mechanisms, first aid during lessons and other most important mechanisms.
Keywords: Physical education, physical fitness, education, medical health